Reclamation of salt‐affected soils in India: Progress, emerging challenges, and future strategies. (13th June 2022) - Kumar, Raj; Singh, Awtar; Bhardwaj, Ajay Kumar; Kumar, Arvind; Yadav, Rajender Kumar; Sharma, Parbodh Chander
Abstract: India is facing economic losses of $US ~ 3.0 billion annually due to the existence of ~ 6.73 million ha of un‐reclaimed salt‐affected soils (SASs). The losses may go up significantly as future projections indicate an increase in the area of SASs to the extent of ~16 million ha by 2050, due to the impact of faulty irrigation practices and climate change. Managing the SASs is one of the major challenges in achieving land degradation neutrality, increasing crop productivity, and sustaining food security in India. Although the problem of SASs has been reduced to some extent through various technological interventions yet further efforts are needed for developing new avenues to further improve the productivity and restrict the expansion of salinity to new areas. The major interventions including application of various ameliorants, growing salt‐tolerant crops and cultivars, installation of sub‐surface drainage, adoption of alternate land‐use systems, and use of land shaping techniques have made significant impact nation‐wide in term of reclamation and productivity enhancement. Despite the achieved success in restoring the productivity of SASs, several constraints at the regional and national level have plagued the reclamation progress. The objective of this review is to compile relevant information available on the use and success of technological interventions to restore SASs. The emerging challenges, and the strategies that would be needed to address the problem of SASs in India are also discussed. This review may help India achieve the Sustainable Development Goals outlined by the UN for land degradation neutrality and food security.